A Comparison of Test Anxiety Related to Physics Exams Among Students at Religious High Schools and Public High Schools: Rasch Analysis and Differential Item Functioning (DIF) - Elsarina Nur Izzati; Moh. Irma Sukarelawan; Melbour Base; Reabbe Ivy Ubao; Suritno Fayanto (Edusainstika, 2026)
Physics test anxiety has been recognized as an important factor affecting students' academic performance; however, evidence regarding differences in physics test anxiety across school contexts remains limited. This study compared physics test anxiety between students from religious-based and public senior high schools and examined whether the Test Anxiety Inventory for Physics (TAIP) functioned equivalently across the two groups using Differential Item Functioning (DIF) analysis within the Rasch measurement framework. A quantitative survey was conducted involving 232 senior high school students from Yogyakarta and Central Java, Indonesia. The Indonesian TAIP was translated through forward–backward translation and administered on a five-point Likert scale. Rasch analysis was employed to estimate person measures, evaluate item fit, and identify DIF, while differences in overall anxiety levels were examined using the Mann–Whitney U test. The findings revealed that students from both school types generally exhibited low levels of physics test anxiety, with no statistically significant difference in overall anxiety levels between religious-based and public senior high schools (U = 6096.50, p = 0.437, Z= -0.776). Nevertheless, the DIF analysis identified three items (WR2, ES5, and LCS3) that functioned differently across school contexts, indicating differences in students' responses to specific aspects of physics test anxiety despite comparable overall anxiety levels. These findings suggest that total anxiety scores may overlook item-level differences. Combining group comparisons with DIF analysis enhances the assessment of physics test anxiety and measurement equivalence across school contexts.